Motivation as a Bridge between Creativity, Environment, and Capital in Shaping Entrepreneurial Interest among Students - Bado, Basri; Isma, Andika; Dewantara, Hajar; Raharimalala, Soussou; Adio, Matthew Olufemi (Quantitative Economics and Management Studies, 2025)
This study aims to examine the influence of creativity, environment, and capital on entrepreneurial interest, with motivation acting as a mediating variable among students of the Faculty of Economics and Business at a university. The sampling technique used was proportional random sampling, and data were collected through questionnaires distributed directly to respondents. The population consisted of active students in the faculty, with a total sample of 109 respondents. Data analysis was conducted using simple linear regression with the assistance of SPSS version 26. The results show that motivation has a significant direct effect on entrepreneurial interest and serves as the primary mediating factor in this study. Creativity was found to have a positive and significant influence on motivation and indirectly contributed substantially to entrepreneurial interest through motivation. The environment emerged as the strongest factor affecting both motivation and entrepreneurial interest. In contrast, capital had the weakest influence on entrepreneurial interest compared to the other variables. Overall, the research model explains 99.7% of the variability in students’ entrepreneurial interest, emphasizing motivation as the key mediating variable linking creativity, environment, and capital to entrepreneurial aspirations.